Obesity results in lower integrin expression in women with polycystic ovarian syndrome during the window of implantation - Hamid, Fazilah Abdul; Mokhtar, Mohd Helmy; Abdul Karim, Abdul Kadir; Ahmad, Mohd Faizal; Abd Aziz, Nor Haslinda; Abdul Wahab, Azantee Yazmie; Abu, Muhammad Azrai (Frontiers in Endocrinology, 2025)
ObjectivePolycystic ovary syndrome (PCOS) is a common endocrine disorder that is characterized by hormonal imbalances and ovarian dysfunction. Obesity is also a prevalent issue that has been linked to the development of PCOS. The present study aimed to investigate the gene expression of αvβ3 integrin, mucin-1, and E-cadherin in obese and non-obese women with and without PCOS.MethodsThis prospective study was undertaken at the Advanced Reproductive Centre at Hospital Canselor Tuanku Muhriz (Universiti Kebangsaan Malaysia) from January 2019 to June 2021. A total of 40 women were recruited for the study and divided equally (n = 10) into four groups, namely, i) control with normal body weight, ii) control obese, iii) PCOS with normal body weight, and iv) PCOS obese. An endometrial tissue sample was collected after 10 days of daily oral micronized progesterone (Utrogestan 200 mg) in the PCOS group. In the fertile or control group, midsecretory phase endometrial biopsy was performed following 7 days post-ovulation. Then, total RNA was isolated from the endometrial tissue. Gene expression was analyzed using RT-qPCR.ResultsThe results showed that the mRNA expression of αVβ3-integrin was significantly decreased in the PCOS obesity group compared to the PCOS normal body weight group and the control normal body weight group. No significant differences were observed in mucin-1 and E-cadherin expression between the groups.Conclusionαvβ3 integrin plays an important role in the development of the window of implantation in obese PCOS individuals. Further research is needed to confirm these results and to identify the potential mechanisms underlying this association.Clinical trial registrationClinicalTrial.gov, identifier NCT04175002.